Participatory design for sustainable social change - Smith, Rachel Charlotte; Iversen, Ole Sejer (Design studies, 2018)
Tendencies in contemporary participatory design suggest a move away from engagement of limited stakeholders in preconfigured design processes and predefined technology outcomes, towards more complex and long-term engagement with heterogeneous communities and larger ecologies of social and technological transformation. Building on core values of participatory design, we introduce three dimensions of engagement of scoping, developing and scaling that we argue can be essential in developing a holistic approach to participatory design as a sustainable practice of social change. The dimensions foreground central aspects of participatory design research that are discussed in relation to a long-term project exploring design and digital fabrication technologies in Danish primary and secondary education. •Assessing challenges in participatory design emphasising political dimensions.•Dimensions of participatory design engagement for sustainable social change.•Impact of long-term participatory design on digital technology in education.